3-D simulation study of single event effects of SiGe heterojunction bipolar transistor in extreme environment. Issue 8 (July 2015) - Zhang, Jin-xin; He, Chao-hui; Guo, Hong-xia; Tang, Du; Xiong, Cen; Li, Pei; Wang, Xin
Highlights: This work performed a 3-D simulation of SEE for domestic SiGe HBT in extreme environment using TCAD tools. Current transient is very severe at low temperature caused by electric field at pn junction and change of mobility. The charge collection will be more sensitive at high temperature and high LET because ionized e-h pairs along ions track increase. Transient pulse caused by diffusion mechanism may have a serious effect on SEE. Abstract: A 3-D simulation of single event effects (SEEs) for domestic Silicon–Germanium heterojunction bipolar transistor (SiGe HBT) in extreme environment is performed with TCAD simulation tools. The influences of environment temperature and linear energy transfer (LET) on SEE are investigated. The combined effects of temperature and LET are also discussed. The results show some interesting phenomena by analyzing collected charges and transient current. The collected charges increase as temperature rises, but the current peaks decline with temperature increasing at base, collector and substrate. However, the peak of emitter transient current rises up and then declines. As LET rises, the collected charges go up linearly, and the transient current peaks also increase but their growth trends are slow. Mobility, carrier ionization and recombination of various regions at different conditions are the main causes of these differences. Current transient is very severe at low temperature. But charge collection is sensitive to high temperature and high LET. Transient pulse caused by diffusion mechanism may have a serious effect on SEEs.